Pengembangan Media Simulasi Berbasis M-Learning pada Materi Transfer Panas di Dalam Struktur Interior Matahari - Khusna, Emi Shofiyatul; Masturi, Masturi (UPEJ Unnes Physics Education Journal, 2021)
This study aims to develop mobile learning (m-learning) based learning media. The media is used as a supplement to astronomy learning at Semarang State University. The content in this media takes one of the astronomical materials, namely the transfer of heat within the sun's interior structure. The interior structure of the sun is an abstract material so that media is needed to facilitate the delivery of material in the learning process. The development model used is ADDIE which includes five stages. They are Analyze, Design, Develop, Implement, and Evaluate. Data obtained from the results of validation of product assessments by experts as well as questionnaires and student learning outcomes. The results of the assessment showed that the media is in the good and very good categories. The student opinion questionnaire showed that the media obtained a very supportive category to be applied in astronomy learning. Procurement of pretest and posttest is carried out to determine student learning outcomes on student understanding of concepts. With the Wilcoxon Signed Rank test, it can be seen that the media can influence student learning outcomes with a low n-gain category.